Distance from a distance: the robustness of psychological distance effects [dataset] - Trautmann, Stefan T. (Universität, 2019)
Psychological distance effects have attracted the attention of behavioral economists in the context of descriptive modeling and behavioral policy. Indeed, psychological distance effects have been shown for an increasing number of domains and applications relevant to economic decision making. The current paper questions whether these effects are robust enough for economists to apply them to relevant policy questions. We demonstrate systematic replication failures for the distance-from-a-distance effect shown by Maglio et al. (2013, Journal of Experimental Psychology: General), and relate them to theoretical arguments suggesting that psychological distance theories are currently too poorly specified to make predictions that are precise enough for economic analyses.
Deposit date: 2019-01-28
Date of collection: Start: 2012 ; end: 2015
Gesehen am 29.01.2019
Keywords: Forschungsdaten; Datenbank